The Role Of Financial Inclusion In The Development Of MSMEs In Madura - Moh. Zaki Kurniawan; M. Boy Singgih Gitayuda (Fakultas Ekonomi Universitas Kadiri, 2021)
This quantitative study aims to find out the development of MSMEs in the Madura region which is based on financial inclusion. The data collection method used a purposive sampling technique in determining the number of samples of MSMEs in the Madura region, especially Bangkalan and Pamekasan regencies. Based on the results of the study which were analyzed using multiple linear regression, it showed that financial inclusion in Madura, which was measured based on the service variables, access to capital, and mentoring, had an impact on the development of MSME businesses in Madura.â€,,,